TEKNIK-TEKNIK DASAR HUMAS DALAM ERA DIGITAL DALAM KONTEKS MANAJEMEN PENDIDIKAN ISLAM - Atik Shaimah Rabiah; Rustam Ibrahim (STKIP Pesisir Selatan, 2026)
This study aims to examine basic public relations techniques and analyze their transformation and relevance in the context of Islamic education management in the digital era. Public relations is a strategic function that plays a role in building an institution's image, establishing relationships with the public, and increasing public trust. This study used a qualitative approach using a literature review of various scientific articles published in the last five years (2020–2025). Data was collected through searches of academic databases and analyzed using content analysis techniques. The study's results indicate that basic public relations techniques, including media relations, publicity, internal communications, community relations, events, and publications, remain relevant in Islamic education management practices. However, these techniques have undergone significant transformation with the development of digital technology, particularly through the use of social media and online communication platforms. Furthermore, this study found that public relations practices in Islamic education are not solely oriented toward communication effectiveness but must also integrate Islamic values such as honesty, trustworthiness, and transparency. Furthermore, this study identified gaps in previous studies, which were still partial and failed to comprehensively integrate basic public relations techniques within the context of Islamic education.